Golden Generation, Worm-Free: Education and Prevention Regarding Worm Infection in Students at Muhammadiyah 5 Junior High School Samarinda: Generasi Emas, Bebas Cacingan: Edukasi dan Pencegahan Mengenai Cacingan pada Siswi di SMP Muhammadiyah 5 Samarinda - Nurul Fitriani; Arden Alvern Tobing; Annisa Nurul Safitri (Jurnal Abdita Naturafarm, 2026)
Helminthiasis remains a significant public health problem in Indonesia, particularly among school-aged children, and can seriously affect growth, intelligence, and academic performance. This study aimed to enhance students’ knowledge and awareness regarding the prevention and management of helminth infections through a health promotion program entitled Golden Generation, Free from Helminths at Muhammadiyah 5 Junior High School Samarinda. The method applied was interactive counseling using PowerPoint presentations and educational leaflets, accompanied by pre-test and post-test assessments to measure students’ understanding before and after the activity. A total of 33 students participated in the program, which covered materials on the definition and types of helminths, symptoms, impacts, prevention through clean and healthy lifestyle practices, and recommendations for regular anthelmintic consumption. The results demonstrated an improvement in students’ knowledge as indicated by higher post-test scores compared to pre-test results, along with high enthusiasm during question-and-answer sessions, quizzes, and discussions. This program concludes that interactive health education is effective in increasing students’ understanding of helminth prevention and has the potential to foster healthy behaviors that support the achievement of a helminth-free generation.